2021
DOI: 10.1073/pnas.2113315118
|View full text |Cite
|
Sign up to set email alerts
|

Photodissociation of dicarbon: How nature breaks an unusual multiple bond

Abstract: The dicarbon molecule (C2) is found in flames, comets, stars, and the diffuse interstellar medium. In comets, it is responsible for the green color of the coma, but it is not found in the tail. It has long been held to photodissociate in sunlight with a lifetime precluding observation in the tail, but the mechanism was not known. Here we directly observe photodissociation of C2. From the speed of the recoiling carbon atoms, a bond dissociation energy of 602.804(29) kJ·mol−1 is determined, with an uncertainty c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 58 publications
3
24
0
Order By: Relevance
“…Our model, which explicitly treats the bound-continuum interaction, provides a compact and physical representation of unimolecular processes (e.g., predissociation) of the highly excited states of C 2 as well as for the mechanisms of elementary C + C reactions and radiative association. The electronic- and vibrational-state-dependent predissociation rates of 3 Π g vibration-rotation levels derived from our valence-hole model are consistent with the experimental observations. , These calculated rates have been used in the modeling of the lifetimes for cometary C 2 , which explains the astronomical observations. The valence-hole-induced vibronic mixing will also have a significant impact on the state-specific collisional dynamics of the C 2 molecule .…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Our model, which explicitly treats the bound-continuum interaction, provides a compact and physical representation of unimolecular processes (e.g., predissociation) of the highly excited states of C 2 as well as for the mechanisms of elementary C + C reactions and radiative association. The electronic- and vibrational-state-dependent predissociation rates of 3 Π g vibration-rotation levels derived from our valence-hole model are consistent with the experimental observations. , These calculated rates have been used in the modeling of the lifetimes for cometary C 2 , which explains the astronomical observations. The valence-hole-induced vibronic mixing will also have a significant impact on the state-specific collisional dynamics of the C 2 molecule .…”
Section: Discussionsupporting
confidence: 77%
“… a Based on the newly measured C 2 bond dissociation energy and the X -state molecular constants, the C­( 3 P ) + C­( 3 P ) limit is taken to be 51,315 cm –1 above the minimum of the X -state potential. All of the specified carbon atomic states belong to the 2s 2 2p 2 electron configuration.…”
Section: Resultsmentioning
confidence: 99%
“…In 2017, Welsh et al found that the v = 12 level of the e 3 Π g state has a reduced lifetime due to predissociation [10]. Later, the photodissociation of C 2 through the e 3 Π g state at high vibrational levels was directly observed in a velocity-map imaging experiment [23]. This process is predicted to be important for cometary C 2 photodissociation.…”
Section: Introductionmentioning
confidence: 99%
“…[22] There are two singlet states, three triplet states, and two quintet states below or around the photodissociation limit, which is 6.36 eV. [23] The Mulliken D 1 Σ + u − X 1 Σ + g band has been well studied. Previous experiments [24][25][26] and theoretical calculations [20] found that the D − X band favors the ∆v = 0 sequence.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1: Molecular parameters derived for the B-R model of the C 2 C state. Based on the newly-measured C 2 bond dissociation energy 38 and the X-state molecular constants, 39 the C( 3 P )+C( 3 P ) limit is taken to be 51315 cm −1 above the minimum of the X-state potential.…”
Section: Global Diabatization Schemementioning
confidence: 99%